Heparin therapy in sepsis and sepsis-associated disseminated intravascular coagulation: a systematic review and meta-analysis - Totoki, Takaaki; Koami, Hiroyuki; Makino, Yuto; Wada, Takeshi; Ito, Takashi; Yamakawa, Kazuma; Iba, Toshiaki (Thrombosis journal, 2024)
Sepsis is a life-threatening condition that affects 49 million people annually. Managing sepsis-associated coagulopathy poses a significant challenge due to its high mortality rates in intensive care. Recent reports suggest that administering heparin may offer potential survival benefits in sepsis and coronavirus disease cases. However, there is currently no established evidence supporting the use of heparin for sepsis. Thus, in this study, we aimed to assess the efficacy of heparin administration in patients with sepsis. A systematic review was conducted following the PRISMA guidelines. The searches included MEDLINE, Cochrane, and Japanese databases up to January 2023. The inclusion criteria consisted of randomized control trials (RCTs) involving adult sepsis patients receiving heparin. The risk of bias was assessed using RoB2, and the data extraction included 28-day mortality and bleeding complications. Out of 1733 initial articles, only three studies met the inclusion criteria. The analysis, which included 426 patients, showed no significant difference in 28-day and in-hospital mortality between the heparin and control groups (risk ratio [RR] = 0.86, 95% confidence interval [CI]: 0.60-1.24). Subgroup analysis of sepsis-associated disseminated intravascular coagulation (DIC) patients (n = 109) also did not show a significant reduction in mortality (RR = 0.84, 95% CI: 0.51-1.38). Heterogeneity was zero, and no publication bias was observed. Additionally, there was significant difference in bleeding complications (RR = 0.49, 95% CI: 0.24-0.99, p = 0.047). This meta-analysis did not demonstrate a survival benefit of heparin administration in patients with sepsis and sepsis-associated DIC. Further investigation into the potential benefits of heparin is warranted. Moreover, the analysis revealed no increase in bleeding risks with heparin administration; instead, a significant reduction in the risk of bleeding was noted. This review was preregistered with PROSPERO (registration: CRD42023385091).